Nuclear control of electron transport chain gene expression - Rowe, Glenn C. (Henry Stewart Talks, 2019)
Introduction to the roles of mitochondria, Subunits of the electron transport chain (ETC) in nuclear & mitochondrial genomes, Transcription of the electron transport chain subunits, Peroxisome proliferator-activated receptor gamma coactivators (PGC-1s), Nuclear respiratory factors (NRFs), Estrogen-related receptor (ESRRs), Mitochondrial transcription factors (Tfam and mtTFB), Yin-Yang (YY-1), Coordinated transcriptional regulation of ETC genes, Summary/Closing Statements